Asian Development Review. - Sawada, Yasuyuki (Asian Development Bank, 2018)
The Asian Development Review (ADR) is a professional journal for disseminating the results of economic development research relevant to Asia and the Pacific. ADR is published twice a year, in March and September, by MIT Press. The ADR is a journal of the Asian Development Bank and the Asian Development Bank Institute.